Classification of cargo lifting machines and mechanisms - V. Sergeev, Vyacheslav; M. Lyashenko, Yuri; K. Mulukhov, Kazbek; V. Gegelashvily, Mikhail (International Journal of Engineering and Technology, 2018)
The studied problem urgency is caused by the fact that now days the cargo-lifting transport machines and mechanisms are considered to be 1 machines group, impeding the study and analysis of the cargo-lifting machines and mechanisms. The article is aimed at the division of the wide class of the lifting-transport machines into 2 classes: cargo-lifting machines and mechanisms and the transport facilities, machines and mechanisms and also the analysis of cargo-lifting machines and mechanisms. The leading approach to this problem study is the collection and generalization of the main information concerning all known constructions of the cargo-lifting machines and mechanisms by classification development of these machines and mechanisms. The cargo-lifting machines and mechanisms, providing the cargo-lifting from one level to another one with the possible shifting in space, restricted by the machine construction were picked out from the transport machines, providing the cargo shifting in the unlimited space one level (horizontal and slightly inclined conveyors, automobile, rail road, sea and river, hydraulic and pneumatic transport ets), resulting in the classification of the cargo lifting machines and mechanisms.Â Â